Ectopic expression of myo-inositol 3-phosphate synthase induces a wide range of metabolic changes and confers salt tolerance in rice. (March 2015) - Kusuda, Hiroki; Koga, Wataru; Kusano, Miyako; Oikawa, Akira; Saito, Kazuki; Hirai, Masami Yokota; Yoshida, Kaoru T.
Highlights: RINO1 catalyzes the first step of inositol biosynthesis. The overexpression of RINO1 gene enhanced the salt tolerance of rice. The overexpression of RINO1 gene increased inositol and inositol related metabolites. The overexpression of RINO1 gene activated the basal metabolic pathways. Abstract: Salt stress is an important factor that limits crop production worldwide. The salt tolerance of plants is a complex biological process mediated by changes in gene expression and metabolite composition. The enzyme myo -inositol 3-phosphate synthase (MIPS; EC 5.5.1.4) catalyzes the first step of myo -inositol biosynthesis, and overexpression of the MIPS gene enhances salt stress tolerance in several plant species. In this study, we performed metabolite profiling of both MIPS -overexpressing and wild-type rice. The enhanced salt stress tolerance of MIPS -overexpressing plants was clear based on growth and the metabolites under salt stress. We found that constitutive overexpression of the rice MIPS gene resulted in a wide range of metabolic changes. This study demonstrates for the first time that overexpression of the MIPS gene increases various metabolites responsible for protecting plants from abiotic stress. Activation of both basal metabolism, such as glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle, and inositol metabolism is induced in MIPS -overexpressing plants. We discuss the relationship between the metabolic changes and the improved salt tolerance observed in transgenic rice.